TSE results complementing the European Union summary report on surveillance for the presence of transmissible spongiform encephalopathies (TSE) - Iceland ... - Icelandic Food And Veterinary Authority MAST (Zenodo, 2020)
This dataset contains TSE surveillance results in cattle, sheep, goats, cervids and other species, and genotyping in sheep, pursuant to Regulation (EC) 999/2001. REPORTING AUTHORITIES CONTRIBUTING TO EACH DATA COLLECTION: TSE_2019_IS: Icelandic Food and Veterinary Authority (MAST) ... : IS; CSV; zoonoses_support@efsa.europa.eu ...